DNA Mini Barcoding untuk Autentikasi Produk Perikanan - Fransisca Victory Kusumaningrum; Laurentia Henrieta Permita Sari Purba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Fisheries production is predicted to continuously increase every year. However, the development of fishery products may result in ingredient substitution where high- value components are replaced with the lower-economic alternatives. Additionally, mislabelling cases also occur when the claims on packaging do not accurately reflect the actual ingredients contained in the product. The use of DNA mini barcoding using the cytochrome c oxidase subunit I (COI) gene has emerged as an innovative solution in species identification, particularly in fishery products with degraded DNA. This technique utilizes short DNA fragments from marker regions ranging from 100-200 bp. By employing shorter marker size, the amplification and species identification process achieve a success rate of approximately 90-95%. DNA mini barcoding offers several advantages, including higher efficiency, speed, and accuracy in identification process, while also being cost-effective. However, this technique has certain limitations such as challenges in distinguishing genetically similar species and the dependence on the quality of the DNA sample. Despite these constrains, DNA mini barcoding serves an alternative for the authentication process of processed food products that contributing to food safety and conservation efforts. Keywords: Authentication; Cytochrome C Oxidase Subunit I; Mini-barcodes DNA; Fish Product